Studies on the rowth Temperature Ranges of Bacteria Isolated from Fresh Sardine at Diffrent Primary Incubation Temperatures - THAMPURAN, NIRMALA; IYER, K MAHADEVA (Fishery Technology, 2017)
The effect of primary mcubation temperature on the growth temperature range wasstudied with reference to 296 bacterial cultures isolated from sardine using streakplate technique. The primary incubation temperature used during bacteriologicalsampling caused a selection of strains according to their growth temperature requirements. Incubation at 8Â°C caused greater recoveries of psychrotrophs while 3rC favoured mesophiles. An incubation temperature of 30Â°C facilitated the growthof both psychrotrophs and mesophiles